Analysis and Solution to the Phenomenon of Ethical Violations by Teachers in the School Environment Against Students - Mira Gunati; Hj. Yeti Kurniati; Hj. Hernawati RAS (Formosa Journal of Social Sciences (FJSS), 2023)
This research reviews the phenomenon of violations of teacher professional ethics, especially cases of sexual violence and harassment against students in 2023. In an effort to understand and analyze these cases, a descriptive research method was used by collecting data from various news sources. The results of the analysis revealed that these violations affected many children and had a serious impact on the educational environment. Success in preventing and dealing with cases like this requires understanding the teacher code of ethics, training, and the need for joint efforts from various related parties